(untitled) (American Journal of Public Diplomacy and International Studies (2993-2157), 2023)
This article explores the influence of English literature on popular culture, encompassing film adaptations, music, fashion, language, social media, and literary tourism. It highlights the enduring impact of renowned literary works such as "Jane Eyre" and "Pride and Prejudice," as well as the cultural resonance of authors like Shakespeare and J.K. Rowling. The references provided offer further insights into the literary classics and scholarly perspectives on the intersection of English literature and popular culture.